Peculiarities of obtaining diamond-(Fe-Cu-Ni-Sn) composite materials by hot pressing - Gevorkyan, E.; Mechnik, V.; Bondarenko, N.; Vovk, R.; Lytovchenko, S.; Chishkala, V.; Melnik, O. (Functional Materials, 2017)
Structure formation processes were investigated depending on sintering temperature in hot pressing of diamond-(Fe-Cu-Ni-Sn) composition and their impact on physical and mechanical properties of obtained composite materials. Properties of the composites, such as hardness, wear resistance and strength limits in compressing and folding were studied. It was found that the composite obtained by hot pressing in the temperature range of 20-1000°C and under a pressure of 0.5-40 MPa had the best properties. The results were compared with mechanical properties of composites obtained earlier by sintering in molds placed in a furnace with hydrogen environment at 800°C during 1 h with subsequent hot repressing under different pressures.